Variação fenotípica em caracteres associados ao sistema de raízes em plântulas de arroz (Oryza sativa L.) - Mistura, Claudete Clarice (2008)
The genetic distance between genotypes is one of the most important pieces of information for a breeding program. This is important at the time of selecting the parental genotypes that will generate the segregating populations. For the phenotypic analysis, 200 rice genotypes were chosen. The experimental design consisted of randomized blocks with three replications. Seeds were germinated in growth chamber at 28 ºC for 72 h and seedlings transferred to a plastic pot containing hydroponic solution, in which they remained until the second leaf emerged. The following characters were evaluated: main root length, secondary root length, 1st and 2nd leaf lengths, coleoptile s length, plant height, shoot and root dry weight. From the results obtained, it can be inferred that there is a correlation between the genotypes of three subspecies evaluated for root related characters and the remaining characters studied. It was also possible to identify contrasting genotypes for root related characters, such as Ligeirão and Farroupilha which are good parental candidates of a mapping population.